2020
DOI: 10.1051/0004-6361/202038160
|View full text |Cite
|
Sign up to set email alerts
|

Precise mass and radius of a transiting super-Earth planet orbiting the M dwarf TOI-1235: a planet in the radius gap?

Abstract: We report the confirmation of a transiting planet around the bright weakly active M0.5 V star TOI-1235 (TYC 4384–1735–1, V ≈ 11.5 mag), whose transit signal was detected in the photometric time series of sectors 14, 20, and 21 of the TESS space mission. We confirm the planetary nature of the transit signal, which has a period of 3.44 d, by using precise RV measurements with the CARMENES, HARPS-N, and iSHELL spectrographs, supplemented by high-resolution imaging and ground-based photometry. A comparison of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

8
2

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 132 publications
0
17
0
Order By: Relevance
“…From Figure 8, we also note that both LHS 1140b and TOI-1235b-a planet recently discovered and characterized by and Bluhm et al (2020)-have densities consistent with rocky compositions, but both reside above the line measured by Cloutier & Menou (2020), where we would have predicted them to have a nonrocky composition. This could suggest that the transition region could lie slightly higher than measured in Cloutier & Menou (2020).…”
Section: Toi-1266c Resides In the Radius Valleymentioning
confidence: 72%
“…From Figure 8, we also note that both LHS 1140b and TOI-1235b-a planet recently discovered and characterized by and Bluhm et al (2020)-have densities consistent with rocky compositions, but both reside above the line measured by Cloutier & Menou (2020), where we would have predicted them to have a nonrocky composition. This could suggest that the transition region could lie slightly higher than measured in Cloutier & Menou (2020).…”
Section: Toi-1266c Resides In the Radius Valleymentioning
confidence: 72%
“…Due to the relatively large TESS pixels spanning 22″ on the sky, fainter visual eclipsing binaries can blend with the nearby bright target stars and produce false positives (barring instrumental artifacts). This is an important consideration, particularly when only a single transiting planet is found in the TESS 27 day time baseline of sector observations, at lower ecliptic latitudes, and away from the ecliptic poles (Lissauer et al 2012;Vanderburg et al 2019;Rodríguez Martínez et al 2020;Hobson et al 2021;Addison et al 2021;Osborn et al 2021;Dreizler et al 2020;Brahm et al 2020;Nowak et al 2020;Teske et al 2020;Sha et al 2021;Gan et al 2021;Bluhm et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The KESPRINT 1 consortium has been a major contributor for the characterization of gas planets (Smith et al 2019;Johnson et al 2018;Barragán et al 2018;Hjorth et al 2019;Eigmüller et al 2017;Smith et al 2017;Grziwa et al 2016;Johnson et al 2016) found by the K2 mission (Howell et al 2014), and currently also for small planets (Gandolfi et al 2019;Esposito et al 2019;Luque et al 2021;Fridlund et al 2020;Carleo et al 2020;Bluhm et al 2020;Van Eylen et al 2021) found by the TESS mission (Ricker et al 2015). Besides small planets, KESPRINT also led the characterization of the first transiting brown dwarf found by TESS, TOI-503b (Šubjak et al 2020).…”
Section: Introductionmentioning
confidence: 99%